2014
DOI: 10.4236/fns.2014.521218
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Yields of Phenolic Compounds during Fermentation Using <i>Saccharomyces cerevisiae</i> Strain 96581

Abstract: Phenylethanol, tyrosol, and tryptophol are phenolic compounds or fusel alcohols formed via the Ehrlich pathway by yeast metabolism. These compounds can yield health benefits as well as contribute to the flavors and aromas of fermented food and beverages. This research shows that Saccharomyces cerevisiae Strain 96581 is capable of producing significantly higher levels of these three compounds when the precursor amino acids were supplemented into either the Chardonnay concentrate for wine-making or the malt conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Phenolic compounds are primarily produced by plants, but some other sources can also produce these compounds as secondary metabolites such as green algae (Onofrejová et al, 2010), yeasts (Banach & Ooi, 2014), endophytes (de Carvalho, Silva, Chagas‐Paula, Luiz, & Ikegaki, 2016), and mushroom basidiomycetes (Palacios et al, 2011; Reis, Martins, Barros, & Ferreira, 2012). Fermentation has been receiving considerable attention for the extraction and production of phenolic compounds due to the fast growth rate, cost effectiveness, easy cultivation, recovery, and eco‐friendly nature of microbial generation of phenolic compounds (Fowler & Koffas, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds are primarily produced by plants, but some other sources can also produce these compounds as secondary metabolites such as green algae (Onofrejová et al, 2010), yeasts (Banach & Ooi, 2014), endophytes (de Carvalho, Silva, Chagas‐Paula, Luiz, & Ikegaki, 2016), and mushroom basidiomycetes (Palacios et al, 2011; Reis, Martins, Barros, & Ferreira, 2012). Fermentation has been receiving considerable attention for the extraction and production of phenolic compounds due to the fast growth rate, cost effectiveness, easy cultivation, recovery, and eco‐friendly nature of microbial generation of phenolic compounds (Fowler & Koffas, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A higher rate of ethanol production in the presence of molasses compared to ethanol production in the presence of glucose also indicates the importance of elements and compounds [21] that were not covered and studied in this study. Ray, RC 2014 [22], Banach, A 2014 [23] and Vilela A. 2019 [24], in their studies of yeast production or growth factors and yeast quality of life, individually and jointly proved that the amount of zinc and magnesium and thiamine in the environment can have a significant effect on the rate of yeast fermentation.…”
Section: Carbon Sourcesmentioning
confidence: 99%
“…Similarly, to tryptophol, phenylethanol, and tyrosol, are phenolic compounds or fusel alcohols formed via the Ehrlich pathway by yeast metabolism. These compounds can yield health benefits as well as contribute to the flavors and aromas of fermented food and beverages [63,65]. Banach and Ooi [65] investigated the possibility of increasing the yield of tyrosol, tryptophol, and phenylethanol in wine (Alexander's Pinot Chardonnay grape juice) and beer [modification of the English Ale recipe composed of chocolate malt barley grain, dried malt extract (DME) and liquid malt extract (LME), supplemented with either the equivalent volume of malt-kiwi purée or with amino acids] using two different yeast strains, and supplementing the substrate with the relevant amino acid precursors or fruits high in these amino acids.…”
Section: Fusel Alcohols Formed Via the Ehrlich Pathwaymentioning
confidence: 99%
“…These compounds can yield health benefits as well as contribute to the flavors and aromas of fermented food and beverages [63,65]. Banach and Ooi [65] investigated the possibility of increasing the yield of tyrosol, tryptophol, and phenylethanol in wine (Alexander's Pinot Chardonnay grape juice) and beer [modification of the English Ale recipe composed of chocolate malt barley grain, dried malt extract (DME) and liquid malt extract (LME), supplemented with either the equivalent volume of malt-kiwi purée or with amino acids] using two different yeast strains, and supplementing the substrate with the relevant amino acid precursors or fruits high in these amino acids. At the end of the work, they found that flavor enhancement and enrichment of antioxidants, in wine and beer, could be achieved through supplementing the fermentation (in the case of beer-fruit-supplemented beer) media with precursor amino acids as well as careful choices of the appropriate yeast strain.…”
Section: Fusel Alcohols Formed Via the Ehrlich Pathwaymentioning
confidence: 99%
See 1 more Smart Citation